Kadar fibrinogen pada penderita penyakit jantung koroner yang dilakukan angiografi - Retta Kristina Sihombing; Zulfikar Lubis; Isfanuddin Nyak Kaoy (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Background : Fibrinogen is a coagulation factor that plays a role in thrombus formation. Many studies have reported that relatively high levels of fibrinogen plays a role in the occurrence of thrombosis in the coronary arteries (myocardial infarction). Atherosclerosis is known by angiographic examination. The purpose of this study to determine whether the levels of fibrinogen in CHD patients with stenosis >70% higher than the ≤70% stenosis.Methods : This analytical cross-sectional study was conducted in H.Adam Malik hospital, during August -November 2013. Subjects were patients with suspected CHD and angiography performed. Criteria for CHD when angiography showed coronary artery stenosis >70% as cases and group ≤70% stenosis as a control. Blood samples were taken 24 hours before angiography to checked fibrinogen levels.Results : In this study, we found significant differences in fibrinogen level between non-CHD 266.85 (47,644) and CHD patients 315.17 (80.184) with p<0.05.Conclusion :. There were a significant difference in the levels of fibrinogen in CHD group compared to the non CHD Key words : CHD; angiography; fibrinogen